Role of Preconditioning Adipose Mesenchymal Stem Cells in Regeneration Disk: a Review Article - Romaniyanto; Hari Basuki Notobroto; Cita Rosita Sigit Prakoeswa; Fedik Abdul Rantam; Dwikora Novembri Utomo; Heri Suroto; Ferdiansyah (Institute of Medico-legal Publications Pvt Ltd, 2021)
Intervertebral disk (IVD) degeneration (IDD) is a degenerative disease and often found in daily practice.The managements that were used so far are only symptomatic and have not been able to solve the diseasecompletely. The use of mesenchymal stem cells (MSCs) has been widely tested as a solution for theregeneration of IVD in IDD. Adipose-derived mesenchymal stem cells (ASCs) are one of the sources ofMSCs which were widely studied as an alternative. One of the factors that can influence the efficiency andcapacity of ASCs in IDD cases is preconditioning. Generally, there were three pre-conditioning strategies ofASCs before being used as therapy, (1) modifying the environment, (2) using Growth Factors, Cytokines,Chemokines, Hormones, (3) using pharmacological and chemical agents. Preconditioning on ASCs canchange its function in various ways. We tried to link all these things together so that we could know the roleof pre-conditioning ASCs in the regeneration disk.